Association of estimated glomerular filtration rate with muscle function in older persons who have fallen. (8th December 2017) - Tap, Lisanne; Boyé, Nicole D A; Hartholt, Klaas A; van der Cammen, Tischa J M; Mattace-Raso, Francesco U S
Abstract: Background: studies suggest that estimated glomerular filtration rate (eGFR) is less reliable in older persons and that a low serum-creatinine might reflect reduced muscle mass rather than high kidney function. This study investigates the possible relationship between eGFR and multiple elements of physical performance in older fallers. Methods: baseline data of the IMPROveFALL-study were examined in participants ≥65 years. Serum-creatinine based eGFR was classified as normal (≥90 ml/min), mildly reduced (60–89 ml/min) or moderately–severely reduced (<60 ml/min). Timed-Up-and-Go-test and Five-Times-Sit-to-Stand-test were used to assess mobility; calf circumference and handgrip strength to assess muscle status. Ancova models adjusted for age, sex, Charlson comorbidity index and body mass index were performed. Results: a total of 578 participants were included. Participants with a normal eGFR had lower handgrip strength than those with a mildly reduced eGFR (−9.5%, P < 0.001) and those with a moderately–severely reduced eGFR (−6.3%, P = 0.033) with mean strengths of 23.4, 25.8 and 24.9 kg, respectively. Participants with a normal eGFR had a smaller calf circumference than those with a mildly reduced eGFR (35.5 versus 36.5 cm, P = 0.006). Mean time to complete the mobility tests did not differ. Conclusions: in this study we found that older fallers with an eGFR ≥ 90 ml/min had smaller calf circumference and up to 10% lower handgrip strength than those with a reduced eGFR. This lower muscle mass is likely to lead to an overestimation of kidney function. This outcome therefore supports the search for biomarkers independent of muscle mass to estimate kidney function in older persons.